The Role of Marketing Research in Achieving Information Awareness - Nagham Dayekh Abd Ali (Universitas Muhammadiyah Sidoarjo, 2025)
Background This study is grounded in the increasing complexity of organizational environments, where economic expansion, technological change, and rising competition intensify the need for accurate information to guide strategic decisions. Specific Background Within this context, marketing research is expected to enhance organizational understanding of markets, consumers, and environmental dynamics, while information awareness enables employees to access, evaluate, and use information effectively. Knowledge Gap Despite these assumptions, limited empirical evidence explains how marketing research contributes to information awareness at the organizational level. Aim This research examines the correlation and effect between marketing research and information awareness among employees of Al Kafeel Printing, Publishing and Distribution House. Results Statistical analysis of data from 26 employees revealed a negative but insignificant correlation between the variables, and no measurable effect of marketing research on information awareness, as indicated by significance values exceeding 0.05. Novelty The study challenges the prevailing belief that marketing research naturally strengthens information awareness, showing that the relationship may be context-dependent and influenced by structural or cultural factors. Implications These findings suggest the need to improve the integration of research outputs into organizational learning processes to enhance informed decision-making and reinforce information-based practices.Highlight : The study shows a negative correlation between marketing research and information awareness. Statistical results confirm no significant effect between the two variables. Increased marketing research does not directly improve employees’ information awareness. Keywords : Marketing Research, Information Awareness, Business Environment, Alkafeel Company